EFFECT OF BENZYLAMINOPURINE AND NUMBER OF SPLITTING OF SHOOT-TIP EXPLANTS OF BANANA (Musa AAA) ON SOMACLONAL VARIATION - Deng , Pio Kur; Ogawi Ojwok Bnyawang, (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2020)
Banana (Musa spp.), is a member of the family Musaceae and it is divided into two types: dessert and cooking bananas. Banana (Musa spp.) is one of the most important of the tropical and subtropical fruits after grapes and citrus. The objective of this study is to evaluate the effect of cytokinin (BAP) concentration and number of explants splitting on induction of somaclonal variation on in vitro propagated banana cvs. Grand Nain. Plant material of banana cv. Grand Nain was selected form greenhouse in Plant Tissue Culture Laboratory at Agriculture Research Corporation (ARC), Wad Medani Sudan. The explants were inoculated on to sterilized solid basal MS medium (Murashige and Skoog’s, 1962) supplemented with different concentrations of cytokinins BAP (1.0 – 10.0 mg/l) and numbers of splitting cycles (first – ten cycles). The result indicated that the highest number of shoots was produced on the second splitting. It was observed that the number of shoots per explants decreased significantly on cultivar Grand Nain except in cycles five and six. The only somaclonal variations observed was mainly dwarfism. The result indicated that the number of shoots regenerated per explants increased significantly with the increase on BAP concentration (6 – 10 mg/l) after 4, 8 and 12 weeks. Results showed that dwarf plants regenerated from the banana cv. Grand Nain restored their normal growth and plant height on MS medium supplemented with GA3 (0.5 – 2.0 mg/l).